2016
DOI: 10.1016/j.fm.2015.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Metaproteomics and ultrastructure characterization of Komagataeibacter spp. involved in high-acid spirit vinegar production

Abstract: Acetic acid bacteria (AAB) are widespread microorganisms in nature, extensively used in food industry to transform alcohols and sugar alcohols into their corresponding organic acids. Specialized strains are used in the production of vinegar through the oxidative transformation of ethanol into acetic acid. The main AAB involved in the production of high-acid vinegars using the submerged fermentation method belong to the genus Komagataeibacter, characterized by their higher ADH stability and activity, and higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(57 citation statements)
references
References 56 publications
3
48
0
Order By: Relevance
“…noted that K. europaeus only appeared at the end of the acetification process when the concentrations of acetic acid increased to levels of above 60 g L −1 and strain diversity tended to be lower. This strain seems to occur in all investigations of submerged culture and trickling generators for vinegar production in which maximum acetic acid concentrations can range from 100 to 140 g L −1 …”
Section: Resultsmentioning
confidence: 99%
“…noted that K. europaeus only appeared at the end of the acetification process when the concentrations of acetic acid increased to levels of above 60 g L −1 and strain diversity tended to be lower. This strain seems to occur in all investigations of submerged culture and trickling generators for vinegar production in which maximum acetic acid concentrations can range from 100 to 140 g L −1 …”
Section: Resultsmentioning
confidence: 99%
“…Generally, Acetobacter and Komagataeibacter could oxidize ethanol to acetic acid during the AAF 33 – 35 . Additives (bran and rice husk) and daily manual stirring could provide glucose and oxygen for the growth of aerobic acid-producing microbes 25 , 36 . Interestingly, we found that Acetobacter and Komagataeibacter also had vital impacts on the formation of acetic acid-2-phenylethyl ester, acetoin, 3-acetoxy-2-Butanone butanone and furfural during the late stage of AAF.…”
Section: Discussionmentioning
confidence: 99%
“…(GTG) 5 -rep-PCR amplification was carried out in a total volume of 25 μl as described by Andrés-Barrao et al (2016) by using the GTG5 primer ( Rademaker et al, 1998 ) (Supplementary Table S1 ). The amplification of the 16S rRNA gene was carried out in a total volume of 20 μl by using the universal primers 27F and 1429R (Supplementary Table S1 ): 200 ng DNA template was added to 18 μl of PCR mixture [2X Taq Polymerase Master Mix (Promega), 0.75 μM each primer] by using the following program: A initial denaturation of 95°C for 5 min followed by 35 cycles with steps of 94°C for 30 s, 55°C for 45 s and 72°C for 1 min 30 s, and a final extension of 5 min at 72°C.…”
Section: Methodsmentioning
confidence: 99%